2013
DOI: 10.4161/cc.25795
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb repressive complex 2 contributes to DNA double-strand break repair

Abstract: Polycomb protein histone methyltransferase, enhancer of Zeste homolog 2 (eZH2), is frequently overexpressed in human malignancy and is implicated in cancer cell proliferation and invasion. However, it is largely unknown whether eZH2 has a role in modulating the DNa damage response. Here, we show that polycomb repressive complex 2 (PrC2) is recruited to sites of DNa damage. this recruitment is independent of histone 2a variant X (H2aX) and the PI-3-related kinases atM and DNa-PKcs. We establish that ParP activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 37 publications
9
119
1
Order By: Relevance
“…Data on PRC function during DDR suggest that PRCs play a role downstream of ATM (Vissers et al, 2012). Consistently, sensitisation to ionising radiation or UV is reported as a consequence of deletions of PRC2 components such as EZH2 (Campbell et al, 2013;Chou et al, 2010). In agreement with an increased sensitivity to DNA damage in the absence of H3K27me3, we found higher frequencies of γH2AX-positive foci in control-treated differentiating Eed-KO ESCs than in differentiating WT ESCs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Data on PRC function during DDR suggest that PRCs play a role downstream of ATM (Vissers et al, 2012). Consistently, sensitisation to ionising radiation or UV is reported as a consequence of deletions of PRC2 components such as EZH2 (Campbell et al, 2013;Chou et al, 2010). In agreement with an increased sensitivity to DNA damage in the absence of H3K27me3, we found higher frequencies of γH2AX-positive foci in control-treated differentiating Eed-KO ESCs than in differentiating WT ESCs.…”
Section: Discussionsupporting
confidence: 77%
“…We next determined the frequency of γH2AX-positive foci in WT and Eed-KO embryoid bodies following GSK-J5 or GSK-J4 treatment as a read out of DSB formation. Consistent with previous reports showing decreased DSB repair in cells lacking EZH2 (Campbell et al, 2013), an integral component of PRC2, we observed that numbers of γH2AX-positive foci were markedly lower in GSK-J4-treated Eed-KO embryoid bodies as compared to those in treated WT embryoid bodies (Fig. 7C).…”
Section: Lack Of H3k27me3 Attenuates Gsk-j4-induced Ddr In Differentisupporting
confidence: 81%
“…Although the colocalisation of PRCs with sites of DNA damage is well established, data linking H3K27me3 directly to DNA damage foci are inconsistent. Two recent studies show increased H3K27me3 at UV-light-induced DNA damage sites (Chou et al, 2010;O'Hagan et al, 2008), whereas two other studies have reported no colocalisation in response to UV or ionising radiation (Campbell et al, 2013;Šustácˇková et al, 2012). This discrepancy could derive from varying experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…DNA double-strand break initiates the recruitment of polycomb group proteins EZH2, SUZ12, CBX8, which constitute a repressive chromatin structure at the sites of DNA damage via H3K27 methylation to block transcription and facilitate DNA repair (Campbell et al, 2013;Chou et al, 2010;O'Hagan et al, 2008). As for H3K4 methylation, it seems to be reversed upon DNA damage.…”
Section: Methylationmentioning
confidence: 99%